Ofloxacin as a Disruptor of Actin Aggresome “Hirano Bodies”: A Potential Repurposed Drug for the Treatment of Neurodegenerative Diseases - Pathak, Samridhi; Parkar, Haifa; Tripathi, Sarita; Kale, Avinash (Frontiers in Aging Neuroscience, 2020)
There is a growing number of aging populations which are more prone to prevalence of the neuropathological disorders which will be affecting nearly about 15 million people by the year 2050. The current treatment regime focuses upon the limited medication for the symptoms of the diseases and not the cause of the disorder. Two major diseases that show a late onset of the symptoms include Alzheimer’s and Parkinson’s disorder which is causing unexpected social and economic impact on the families. A large number of researches in last decade has focused upon the role of amyloid precursor protein (APP), Aβ-plaque and intraneuronal neurofibrillary tangles (tau-proteins). However, there is very few understandings of actin-associated paracrystalline structures formed in the hippocampus region of the brain and is called as Hirano bodies. These actin-rich inclusion bodies are known to modulate the synaptic plasticity and employs conspicuous effects on long term potentiation (LTP) and paired-pulse paradigms. They have been predominantly associated with dendrites and cell bodies of hippocampal pyramidal neurons in the pathological conditions such as Alzheimer's disease (AD), Amyotrophic Lateral Sclerosis (ALS), Parkinson's disease (PD), alcoholism and normal aged individuals. Since the current known drugs have very little effect in controlling the progression of these diseases, there is a need to develop therapeutic agents which can have improved efficacy and bioavailability, can transport across the blood-brain barrier (BBB) and simultaneously reduce the ill-effects of pharmacological compounds for treatment of actin associated neurodegenerative disorders. Finding alternative functions to the already existing FDA approved molecules for reversing the progression of age-related proteinopathies is of importance, provided they have a proper drug delivery vehicle to be able to cross the BBB. In the current study we decipher the role of a broad-spectrum general antibiotic (Ofloxacin) on actin polymerization dynamics using various biophysical techniques like Right angle light scattering (RLS), Dynamic light scattering (DLS), Circular dichroic (CD) spectrometry, Isothermal titration calorimetry (ITC), Scanning electron microscopy (SEM) etc. We have also performed in silico docking studies to deduce a plausible mechanism of the drug binding to the actin.